Activism: terms of origin of public motions - Mordovets, M. V.; Мордовец, М. В.; Мордовець, М. В. (Одеса: Фенікс, 2015)
In the article it is represented the analysis of the conditions of appearance of social movements, individual and group activity. The focus of the article is on the conceptual approaches that has been formed in social psychology and are actively used by the political science. It is considered that the selection of the mean of explanation of the nature and mechanisms of social action that appeared by the influence of cultural, social, structural, mental-psychological factors is a high- powered element through the research of the socio-political activism.
Mordovets M. V Activism: terms of origin of public motions / M. V. Mordovets // Актуальні проблеми політики зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), Л. І. Кормич (заст. голов. ред.), М. А. Польовий (відп. секр.) [та ін.] ; НУ «ОЮА», Південноукр. центр гендер. проблем. – Одеса : Фенікс, 2015. – Вип. 55. – С. 139-146.
Keywords: социальные движения; индивидуальная и групповая активность; социальная психология; выбор средства объяснения природы и механизмов социального действия; соціальні рухи; індивідуальна та групова активность; соціальна психологія; вибір засобу пояснення природи і механізмів соціальної дії; social movements; individual and group activity; social Psychology; choice of tools and mechanisms to explain the nature of social action